Impaired lipid biosynthesis hinders anti-tumor efficacy of intratumoral iNKT cells - Sicheng Fu (Nature Portfolio, 2020)
Lipid metabolism has been linked to iNKT function largely as it impacts processing and presentation of lipids they recognize. Here the authors show that iNKT-intrinsic lipid biosynthesis is important for their function but is impaired in tumors, and its restoration with PPARγ agonist drugs promotes anti-tumor iNKT response.